Cisd2: a promising new target in Alzheimer's disease†. Issue 2 (11th May 2020) - Nobili, Annalisa; Krashia, Paraskevi; D'Amelio, Marcello
Abstract: The CISD2 gene encodes the CDGSH iron‐sulfur domain‐containing protein 2. Cisd2 is involved in mammalian lifespan control, the unfolded protein response, Ca 2+ buffering, and autophagy regulation. It has been demonstrated previously that Cisd2 deficiency causes an accelerated ageing phenotype characterised by the accumulation of damaged mitochondria, while Cisd2 overexpression leads to mitochondrial protection against typical age‐associated alterations. Accumulating data suggest that neuronal amyloid‐beta (Aβ) deposition, Ca 2+ dysregulation, impairment of autophagic flux, and accumulation of damaged organelles including mitochondria play an important role in Alzheimer's disease (AD) pathogenesis. In a recent issue of The Journal of Pathology, Yi‐Fan Chen and collaborators put together all these experimental observations and demonstrated that Cisd2 overexpression attenuates AD pathogenesis by guaranteeing mitochondrial quality and synaptic functions. The authors report convincing evidence to highlight the role of Cisd2 in Aβ‐mediated mitochondrial damage and, interestingly, this neuroprotection could be dependent on other molecular mechanisms beyond the canonical and previously described roles of Cisd2. Collectively, these data open up new avenues in neuroprotection and highlight Cisd2 as a promising new target in AD. © 2020 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.